Smart Logistics 5.0: Integrated Transportation Innovation for Global Supply Chain Efficiency - Kasrim (PT. Anagata Sembagi Education, 2025)
Smart Logistics 5.0 represents the latest evolution in supply chain management, integrating digital technologies (IoT, edge computing, AI, blockchain, big data) and physical automation (robotics, autonomous vehicles, drones) with human-centered principles, sustainability, and resilience. This systematic literature review examines publications from 2020–2025 to understand how multimodal integrated transport innovations improve efficiency, transparency, and resilience in global supply chains. The review methodology involved searches in major databases (Scopus, Web of Science, Google Scholar) using keywords related to Industry 5.0, Smart Logistics, integrated transport, IoT, blockchain, and autonomous logistics; records were then screened against clear inclusion criteria and analyzed thematically. Findings indicate that IoT combined with edge computing enhances operational visibility and real-time orchestration; AI and big data analytics improve forecasting accuracy and route optimization; and blockchain supports traceability and administrative automation via smart contracts. Furthermore, multimodal transport integration (sea, land, air, rail) enabled by digital platforms has been shown to lower door-to-door costs, accelerate deliveries, and bolster network adaptability to disruptions. Major barriers include fragmented data standards, high upfront investment needs, regulatory issues (notably for autonomous vehicles and drones), and workforce skills gaps. Distinct from earlier reviews, this study emphasizes the role of multimodal transport innovation within the Smart Logistics 5.0 framework as a key driver of a more efficient, resilient, and sustainable global supply chain.